ANTIMICROBIAL ACTIVITIES OF SOME MEDICINAL PLANTS OF WEST BENGAL - SANKAR KUMAR DEY; DEBDULAL BANERJEE; SOURAV CHATTAPADHYAY; KRISHNENDU BIKASH KARMAKAR (International Journal of Pharma and Bio Sciences, 2010)
In rural and backward area of West Bengal, India several plants are commonly used as herbal medicine for the treatment of infectious diseases. Four such plants commonly used by the people of the area were screened for potential antibacterial activity. Antibacterial activity of both aqueous and methanol extracts of the plants parts were used for screening. The plants screened were Psidium guajava, Andrographis paniculata, Terminalia arjuna and Adhatoda vasica. Antibacterial activity was tested against six strains of both Gram positive and Gram negative bacteria. The susceptibility of the microorganisms to the extracts of these plants was compared with each other and with selected antibiotics. The result showed that, the methanol extracts of selected medicinal plants exhibited high activity against the tested organisms rather than aqueous extract of those plants. So, the minimum inhibitory concentration (MIC) of the methanol extract of selected plants was studied. Extract from Terminalia arjuna showed higher antimicrobial activity than the extract of Psidium guajava.